Bead-based cellular analysis, sorting and multiplexing - Rosario M. Sanchez Martin; Mathilde Muzerelle; Nutcha Chitkul; How, Siew Eng; Stifun Mittoo; Mark Bradley (WIiley -VCH Verlag GmbH & Co. KGaA, Weinheim, 2005)
Functionalized cross-linked polystyrene microspheres were synthesized, fluorescently labelled and delivered into cells to function as cellular tags and probes (see figure). This allowed the effective delivery of foreign materials into intact mammalian cells, without the need for delicate procedures such as micro-injection, and did not disrupt cell physiology.